1994
DOI: 10.1046/j.1471-4159.1994.63041392.x
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Transporter Isoform Expression in Huntington's Disease Brain

Abstract: Several reports have suggested a characteristic decrease in glucose use in the striatum of patients with Huntington's disease (HD) may contribute to the cellular atrophy of the caudate and putamen. We examined the expression of the two major glucose transporter isoforms of brain, GLUT1 and GLUT3. GLUT1 is found largely in capillary endothelial cells and to a lesser extent in the brain parenchyma, whereas GLUT3 is localized primarily in neurons. Membranes prepared from postmortem samples of HD caudate and corte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 21 publications
0
20
0
1
Order By: Relevance
“…To the best of our knowledge, there is no evidence suggesting an impairment of primary glucose metabolism in R6/1 HD mice. Additionally, in human HD patients with mild neuropathological features of HD (grade 1), there is no difference in the expression of the GLUT1 and GLUT3 glucose transporters compared with control subjects (Gamberino and Brennan, 1994). Moreover, our analysis of cortical plasticity, based on a within-subject approach rather than a comparison between WT and HD mice, dissociates defects in cortical plasticity from the separate issue of basal glucose metabolism.…”
Section: Discussionmentioning
confidence: 87%
“…To the best of our knowledge, there is no evidence suggesting an impairment of primary glucose metabolism in R6/1 HD mice. Additionally, in human HD patients with mild neuropathological features of HD (grade 1), there is no difference in the expression of the GLUT1 and GLUT3 glucose transporters compared with control subjects (Gamberino and Brennan, 1994). Moreover, our analysis of cortical plasticity, based on a within-subject approach rather than a comparison between WT and HD mice, dissociates defects in cortical plasticity from the separate issue of basal glucose metabolism.…”
Section: Discussionmentioning
confidence: 87%
“…Our studies suggest that HD progression could be affected by GLUT3 expression level, and functionality as in neurones glucose uptake is mainly dependent on this transporter. Indeed, a post-mortem brain study found a significant reduction in GLUT3 levels in the caudate of Grades 1 and 3 HD brain, but not in the cortex (35). …”
Section: Discussionmentioning
confidence: 99%
“…Studies on post-mortem brain tissue or positron emission tomography imaging analyses revealed reduced cerebral metabolic activity in cortex and striatum of symptomatic HD patients and also in pre-symptomatic subjects, so even before the onset of pathological symptoms [23, 24, 25, 26]. Moreover, Gamberino and Brennan [27] described decreases in glucose transporter levels by post-mortem analysis in caudate and not in cerebral cortex of HD brains; these decreases were not closely related to brain atrophy but can be associated to changes in transporter expressions. Interestingly, in a recent study on HD patients, a correlation was found between the onset of the disease and the copy number of the GluT3 gene [28].…”
Section: Introductionmentioning
confidence: 99%